LEGISLASI SYARI’AT ISLAM MELALUI PERDA SYARI’AH - Irma Suryani (Institut Agama Islam Negeri Batusangkar, 2018)
Basically, Islamic institution had became the demand and thinking process of Moslem people in law. Their consideration to follow the Islamic orders never die socially and culturally. This showed that the spread out of Islamic values, local wishes and customes had big relationship to serve the law concept universally. It could be said that this law maight be accepted by anyone whereever they are. Socially, a law meant a reflection of convection in societies that they believed as one important thing in their daily life in society and state. It was clear that adapted law by this society had to be able to respond the societies’ aspiration in order to face the social development in the future.